Anki app and vocabulary learning in EFL students. - Zapata Vicente, Maritza Inés (2023)
In a world where technology plays an increasingly significant role in education, this study investigated whether the Anki app could serve as a valuable tool for language learners. The research employed a quasi-experimental design, incorporating both quantitative and qualitative analyses to provide a comprehensive assessment. Twenty- four students from First baccalaureate who study English as a Foreign language participated in the study. Quantitative data analysis revealed that Anki app integration resulted in significant improvements in vocabulary acquisition and retention. The students' pretest and posttest scores demonstrated substantial growth, indicating the app's positive impact on language proficiency. Qualitative insights from students’ perceptions gathered through a questionnaire, highlighted the convenience and user- friendliness of the Anki app, but also identified challenges such as technical issues and the need for more engaging content. These findings contributed to a nuanced understanding of the app's implementation in EFL settings. Overall, this research sheds light on the potential benefits and limitations of incorporating the Anki app into vocabulary instruction.